Personalized Pathways to Proficiency: Exploring the Synergy of Adaptive Learning and Artificial Intelligence in English Language Learning - Martha Betaubun; Desy Eva Laila Rokhmah; Jarot Budiasto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This research aims to explore the potential of an artificial intelligence (AI) platform in revolutionizing education and evaluating student performance, with a specific focus on English learning. The study adopts a qualitative research method, employing a comprehensive literature review to gain insights into the role of AI in language education. The findings reveal that AI technology holds promise as a powerful tool for enhancing English learning among students. The discussion encompasses various studies supporting the use of AI-based applications, websites, Virtual Reality technology, and other AI-driven learning and teaching systems to improve students' English skills. However, the research acknowledges the limitation of not extensively examining the full extent of AI's role in students' English learning. As a suggestion for future research, further investigations are proposed to thoroughly assess the precise impact of AI in improving students' English proficiency.